Inflammatory potential of the diet and self-rated quality of life in Italian adults - Giampieri, Francesca; Godos, Justyna; Caruso, Giuseppe; Olvera-Moreira, Marco Antonio; Furnari, Fabrizio; Di Mauro, Andrea; Domínguez Azpíroz, Irma; Zambrano-Villacres, Raynier; Frias-Toral, Evelyn; Galvano, Fabio; Grosso, Giuseppe (Frontiers in Nutrition, 2026)
BackgroundDietary quality is widely acknowledged as a key factor in maintaining good health. Recommendations that promote plant-based eating patterns are largely grounded in evidence showing that dietary choices can modulate the immune function. In line with such a hypothesis, diet may be considered as a potential driver of persistent low-grade inflammation. Quality of life (QoL), on the other hand, serves as a broad indicator that encompasses both physical and psychological wellbeing.AimThe purpose of this cross-sectional study was to examine the relationship between the inflammatory potential of the diet and QoL in a population sample of Italian adults.DesignA total of 1,936 participants completed a 110-item food frequency questionnaire to assess eating habits. The inflammatory potential of their diet was calculated using the dietary inflammatory score (DIS). Quality of life was measured with the Manchester Short Appraisal (MANSA).ResultsHigher DIS values, reflecting a more pro-inflammatory diet, were linked to reduced likelihood of reporting high QoL (OR = 0.56; 95% CI: 0.40–0.78). Several specific domains of QoL, including general life satisfaction, social relationships, personal safety, satisfaction with cohabitation, physical health, and mental health, also showed significant associations with DIS.ConclusionThe findings suggest an association between the inflammatory potential of the diet and QoL.